Dasatinib plus Peg‐Interferon alpha 2b combination in newly diagnosed chronic phase chronic myeloid leukaemia: Results of a multicenter phase 2 study (DASA‐PegIFN study). (10th October 2022) - Roy, Lydia; Chomel, Jean‐Claude; Guilhot, Joëlle; Guerci‐Bresler, Agnès; Escoffre‐Barbe, Martine; Giraudier, Stéphane; Charbonnier, Aude; Dubruille, Viviane; Huguet, Françoise; Johnson‐Ansah, Hyacinthe; Lenain, Pascal; Ame, Shanti; et al.
Summary: Superior rates of deep molecular response (DMR) have been reported with the combination of tyrosine kinase inhibitors and pegylated‐interferon‐alpha (Peg‐IFN) in patients with newly diagnosed chronic phase‐chronic myeloid leukaemia (CP‐CML). In this setting, this study investigated the efficacy and safety of dasatinib combined to Peg‐IFN‐α2b (Dasa‐PegIFN, NCT01872442). A total of 79 patients (age ≤65 years) started dasatinib; 61 were eligible for Peg‐IFNα‐2b add‐on therapy at month 3 for a maximum 21‐months duration. Dasatinib was continued thereafter. The primary endpoint was the cumulative rate of molecular response 4.5 log (MR 4.5 ) by 12 months. The results are reported for the 5‐year duration of the study. Grade 3 neutropenia was frequent with the combination but did not induce severe infection (one of grade 3). Other adverse events were generally low grade (4% of grade 3–4) and expected. Seventy‐nine per cent and 61% of patients continued the Peg‐IFN until months 12 and 24, respectively. Overall, at these time points, MR 4.5 rates were 25% and 38%, respectively. Thereafter, 32% and 46% of patients achieved a sustained (≥2 years) MR 4.5 or MR 4, respectively. This work established the feasibility and high rates of achievement of early and sustained DMR (a prerequisite for treatment‐free‐remission) with dasatinib and Peg‐IFNα‐2b combination as initial therapy.